Preliminary design study of four-seater helicopter tail rotor drivetrain [electronic resource] - 443548 Azizul Syahrin Ahmad Rami (2007)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Automotif)) - Universiti Teknologi Malaysia, 2007